(untitled) (Journal of the College of Basic Education, 2022)
It dealt with various aspects of the educational process, indicating that there is a growing interest in teaching methods, strategies and methods, as well as tendencies towards adopting the latest teaching methods in teaching various academic subjects, including the subjects that constitute the Art Education Teacher Preparation Program, which aims to develop different aspects in the personality of the learner in particular. What is related to artistic taste, as the current goals of teaching these subjects, especially artistic taste, have become. Therefore, the researcher sets out to define the problem of his research by experimenting and applying the individual (self) learning strategy in developing artistic taste.